Deep Ultraviolet Photodetector with Ultrahigh Responsivity based on a Nitrogen‐Doped Graphene‐Modified Polypyrrole/SnO2 Organic/Inorganic p–n Heterojunction. Issue 9 (30th January 2023) - Fu, Shihao; Song, Renjing; Wang, YueFei; Han, Yurui; Gao, Chong; Ma, Jiangang; Xu, Haiyang; Li, Bingsheng; Shen, Aidong; Liu, Yichun
Abstract: Deep ultraviolet monitoring is realized via a high crystal quality SnO2 microwire (MW)‐based photodetector (PD). This is then combined with 2D nitrogen‐doped graphene (NGr), conducting polymer polypyrrole (PPy), and an in situ polymerization‐fabricated composite film PPy‐NGr to construct an organic–inorganic p–n heterojunction PD. The long response time brought on by the oxygen adsorption of SnO2 MW is greatly decreased via coating with the aforementioned materials. A defect response is created by the surface dangling bonds of SnO2 MW, which can be effectively suppressed by the PPy. Absorption in the deep ultraviolet region (<240 nm) by PPy results in a blue shift of the response peak of the PPy/SnO2 heterojunction PD compared to that of a single SnO2 PD. The introduction of NGr improves the detection performance by providing a smoother energy band migration to reduce photogenerated carrier recombination and stacking at the potential barrier. The ultrahigh responsivity of PPy‐NGr/SnO2 PD is 4594.25 A W −1 and the detectivity is 6.47 × 10 11 Jones, 40 and nine times greater, respectively, than those of a PPy/SnO2 PD under a 5 V reverse bias and 240‐nm light irradiation (18.75 µW cm −2 ). The novel strategy provides a reference for the future design of high‐performance heterojunction PDs. Abstract : Deep ultraviolet monitoring is realized via a high crystal quality SnO2 microwire‐based photodetector and constructed organic‐inorganic p–n heterojunction with polypyrrole (PPy), nitrogen‐doped graphene (NGr), and an in‐situ polymerization formed composite film PPy‐NGr. PPy can modify the SnO2 response band and suppress defect energy level response. NGr is proved to be able to adjust the energy band arrangement of heterojunction.